2013
DOI: 10.1186/1476-069x-12-30
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of occupational manganese exposure and alcohol drinking aggravates the increase of liver enzyme concentrations from a cross-sectional study in China

Abstract: BackgroundOver exposure to manganese (Mn) can damage the human central nervous system and potentially cause liver toxicity. Alcohol drinking is also one of the well-known harmful factors to hepatic organism. The interaction between Mn exposure and alcohol consumption to liver function was investigated in this study.MethodsA total of 1112 on-the-spot workers were included in the cross-sectional survey from a large scale of manganese exposed workers healthy cohort (MEWHC) in a ferro-manganese refinery company. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…A total of 843 occupational Mn-exposed workers were included in this cross-sectional epidemiological study; they formed one part of our Mn-exposed workers healthy cohort (MEWHC), as previously described 27. To compare the cognitive function of Mn-exposed workers with that of the healthy population, we recruited a group of union 293 workers with no Mn exposure from a sugar refinery in the same region as the Mn-exposed workers.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 843 occupational Mn-exposed workers were included in this cross-sectional epidemiological study; they formed one part of our Mn-exposed workers healthy cohort (MEWHC), as previously described 27. To compare the cognitive function of Mn-exposed workers with that of the healthy population, we recruited a group of union 293 workers with no Mn exposure from a sugar refinery in the same region as the Mn-exposed workers.…”
Section: Methodsmentioning
confidence: 99%
“…Elevated Mn exposure is linked to adverse health outcomes. In recent years, epidemiological evidence has emerged indicating that Mn toxicity involves the central nervous system, the respiratory system, and liver function, and is, therefore, a relevant occupational health concern 3‐8 …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, epidemiological evidence has emerged indicating that Mn toxicity involves the central nervous system, the respiratory system, and liver function, and is, therefore, a relevant occupational health concern. [3][4][5][6][7][8] Despite demonstrated neurological deficits caused by elevated exposure to Mn, limited research is available on Mninduced cardiovascular dysfunction. A series of earlier experiments on animal models, including rat, cat, pig, rabbit, and dog, indicated that Mn salts can affect cardiovascular function primarily by affecting myocardial contraction, resulting in a fall in blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Histopathologic examinations revealed that МnO 2 nanoparticles had toxic influence on liver and kidneys [46]. There is an assumption that manganese is transported to organs with significant mitochondria content (to liver, pancreas and hypophysis in particular) where it is accumulated very fast [47].…”
Section: Cerebellum Of a Rat At Intragastric Introduction Of Nanodispmentioning
confidence: 99%